Cardiac Natriuretic Peptide Profiles in Chronic Hypertension by Single or Sequentially Combined Renovascular and DOCA-Salt Treatments - Cerrudo, Carolina S.; Cavallero, Susana; Rodríguez Fermepín, Martín; González, Germán E.; Donato, Martín; Kouyoumdzian, Nicolás M.; Gelpi, Ricardo J.; Hertig, Cecilia M.; Choi, Marcelo R.; Fernández, Belisario E. (Frontiers in Physiology, 2021)
The involvement of natriuretic peptides was studied during the hypertrophic remodeling transition mediated by sequential exposure to chronic hemodynamic overload. We induced hypertension in rats by pressure (renovascular) or volume overload (DOCA-salt) during 6 and 12 weeks of treatment. We also studied the consecutive combination of both models in inverse sequences: RV 6 weeks/DS 6 weeks and DS 6 weeks/RV 6 weeks. All treated groups developed hypertension. Cardiac hypertrophy and left ventricular ANP gene expression were more pronounced in single DS than in single RV groups. BNP gene expression was positively correlated with left ventricular hypertrophy only in RV groups, while ANP gene expression was positively correlated with left ventricular hypertrophy only in DS groups. Combined models exhibited intermediate values between those of single groups at 6 and 12 weeks. The latter stimulus associated to the second applied overload is less effective than the former to trigger cardiac hypertrophy and to increase ANP and BNP gene expression. In addition, we suggest a correlation of ANP synthesis with volume overload and of BNP synthesis with pressure overload-induced hypertrophy after a prolonged treatment. Volume and pressure overload may be two mechanisms, among others, involved in the differential regulation of ANP and BNP gene expression in hypertrophied left ventricles. Plasma ANP levels reflect a response to plasma volume increase and volume overload, while circulating BNP levels seem to be regulated by cardiac BNP synthesis and ventricular hypertrophy.